The Chronotope of Home in The Rainbow: Place, Time and Identity - Marina Ragachewskaya (Études Lawrenciennes)
Home in contemporary culture is acquiring ontological value due to our changing globalized world. In Lawrence’s fiction, the concept of home is an important metaphor of self and identity. In this paper, I apply Mikhail Bakhtin’s theory of the chronotope to elucidate the meaning and role of home in identity creation, drawing on a reading of The Rainbow. The static (place) and the dynamic (time) qualities of the home chronotope are catalysts of the action and feeling for most of the Brangwen family members. Home is mostly an enclosed static space, which magnetically draws its inhabitants. Life whirls and bubbles around it, making it dynamic as well – from the nineteenth-century agricultural domestic arrangements to the change and flux of the early twentieth century. Thus the stability of home is constantly disrupted by changes, newcomers, by life itself. Ursula’s identity as one of the Brangwen women whose eyes remain turned to the outside world, but who are their own selves only within the enclosure of their home, is formed by the complementary drives of leave taking and home-coming. The threshold, both the symbolic image and Bakhtinian chronotope, is constantly present in the narration, marking the crucial moments in the characters’ lives. Ursula’s identity undergoes such changes and becomes firmly established as a Brangwen woman.